TEACHING THE PATIENT WITH CARDIAC INSUFFICIENCY: STRATEGIES USED IN NURSING INTERVENTIONS - Ana Carla Dantas Cavalcanti; Cristina Silva Arruda (Universidade Federal do Paraná, 2012)
The aim of this study was to identify nursing intervention strategies used in the teaching of the patient with cardiac insufficiency. It is an integrative review with a quanti-qualitative approach. Of the 270 scientific articles found, 47 were selected, 51% are experimental and observational studies, 25% reviews and 15% case reports. 57% came from American magazines, 34% from European magazines, and 6% from Brazilian magazines. The most-used strategies were individual discussion (47%), telephone follow-up (32%) and use of written material (25%); these were developed in 46% of cases in Cardiac Insufficiency Clinics. The studies demonstrate the actions aimed at teaching and following up patients, and reflect the growing concern in discussion of intervention strategies which focus on the improvement of the quality of life of those patients with Cardiac Insufficiency. However, it is necessary for the research to consider the analysis of the effectiveness of implementation of the strategies.